Inter‐numerology interference in OFDM‐IM systems - Seda Dogan‐Tusha; Armed Tusha; Ertugrul Basar; Saud Althunibat; Khalid Qaraqe; Hüseyin Arslan (IET Communications, 2021)
Abstract In 5G and beyond communication systems, distinct numerologies can coexist to serve diverse requirements for users and applications. However, the inter‐numerology interference (INI) is a main challenge that significantly impacts the system performance. Therefore, the performance under INI has become an essential evaluation metric for the suitability of the different transmission schemes in the future communication systems. This paper analyzes the impact of INI on the performance of orthogonal frequency division multiplexing with index modulation (OFDM‐IM) systems. Specifically, an analytical expression of the INI level in OFDM‐IM systems is presented as a function of the subcarrier activation ratio (SAR) and subcarrier activation probability (SAP). Furthermore, aiming at reducing the INI level, an adaptive subcarrier mapping scheme (SMS) is proposed based on the conventional combinatorial mapping scheme. Moreover, analysis and evaluation of SAR and SAP are performed regarding the requirements of 5G and beyond services. It is proved that the INI level in OFDM‐IM systems is highly dependent not only on the number of active subcarriers but also on their position in an OFDM block.